Pengaruh Diskon Harga Dan Endorsment Terhadap Keputusan Pembelian Di Tiktok : (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Islam UIN STS Jambi) - Rizky Fitra Ananda; Erwin Saputra Siregar; Ogi Saputra (JOURNAL SAINS STUDENT RESEARCH, 2023)
With the advancement of technology and the growth of the internet, short videos have gradually influenced and even replaced current mainstream media such as magazines, newspapers, television, and others, due to their fast distribution speed, wide distribution reach, and a large number of participants. A report by We Are Social shows that the number of active social media users in Indonesia reached 167 million people in January 2023. Buying and selling are everyday activities that involve the exchange of both necessary and less essential products. Year after year, consumer consumption continues to rise. Because of this, a significant number of online sellers have emerged, making it easier for buyers to shop online. E-commerce offers advantages to consumers, such as saving time when shopping, as it can be done online without the need to visit physical stores. Consumers can compare products more accurately. E-commerce platforms offer a wide range of stores selling similar products, allowing consumers to easily compare products in terms of quality and price from one store to another. One popular type of online store is the Tiktok Shop. Recently, people have been excited about the surge in online shopping conducted through video and live streaming via the Tiktok app. This is why people are interested in shopping at online stores. TikTok Shop, the latest addition to the app, was launched in April 2021. The purpose of this feature is to enable users to make buying and selling transactions within the TikTok app. At that time, few people were aware of this feature because it was still very new. The lack of appeal in the products being sold and their high prices made some students less inclined to make purchases on Tiktok. This research aims to investigate the influence of price discounts and endorsements on purchasing decisions on Tiktok. The research method used is descriptive quantitative. A sample of 100 respondents was selected using incidental sampling. This research used SPSS version 22 for data analysis. The results of the research indicate that price discounts and endorsements have a positive and significant influence on purchasing decisions. Based on data analysis in this research, these variables are valid and reliable. The classic assumption tests in this research show that the data is normally distributed, there is no heteroskedasticity, and there is no multicollinearity.